Effect of corticosteroids on the outcome of patients with advanced non–small cell lung cancer treated with immune-checkpoint inhibitors. (March 2021) - Skribek, Marcus; Rounis, Konstantinos; Afshar, Soren; Grundberg, Oscar; Friesland, Signe; Tsakonas, Georgios; Ekman, Simon; De Petris, Luigi
Abstract: Introduction: We analysed patients with advanced non–small cell lung cancer (NSCLC) who were treated with immune-checkpoint inhibitors (ICIs) to address the effect of the timeline and reason for corticosteroid administration on survival outcomes. Methods: We retrospectively collected clinical data of non-oncogenic driven, advanced NSCLC patients treated with ICIs at Karolinska University Hospital, including the timeline and reason for steroid administration. Steroid administration was defined as > 10 mg prednisolone equivalent for ≥10 days. We subcategorized patients based on the aetiology of steroid administration into three subgroups: a) steroids for supportive reasons but not for cancer palliation; b) steroids for the palliation of cancer-related symptoms; c) steroids for the management of immune-related adverse events (irAEs). Furthermore, to analyse the timeline, patients were categorised into two groups; those who received corticosteroids within 2 weeks before until 2 days after ICI initiation and those who received steroids later during their treatment course. Results: Analysed data from 196 patients showed 46.3% of patients received corticosteroids. Steroid administration due to irAEs did not affect overall survival (OS) (p = 0.38) compared with the steroid naïve group. Only steroid administration for the palliation of cancer-related symptoms was an independent predictor for shorter OS (HR = 2.7; 95% CI, 1.5–4.9). The timeline of steroid administration did not affect OS (p = 0.456) in our cohort. Conclusions: Steroids due to irAEs do not appear to hamper ICI efficacy. However, the administration of high-dose steroids to palliate malignancy-associated symptoms might reflect the dismal prognosis of this patient group. Highlights: Steroid administration for cancer palliation was linked with poor patient outcomes. Steroid administration due to immune-related adverse events did not affect patient survival outcomes. Careful patient selection is warranted before immunotherapy initiation.